A genome-wide survey of structural variation between human and chimpanzee - Newman, Tera L.; Tuzun, Eray; Morrison, V. Anne; Hayden, Karen E.; Ventura, Mario; McGrath, Sean D.; Rocchi, Mariano; Eichler, Evan E. (Genome Research, 2005)
Structural changes (deletions, insertions, and inversions) between human and chimpanzee genomes have likely had a significant impact on lineage-specific evolution because of their potential for dramatic and irreversible mutation. The low-quality nature of the current chimpanzee genome assembly precludes the reliable identification of many of these differences. To circumvent this, we applied a method to optimally map chimpanzee fosmid paired-end sequences against the human genome to systematically identify sites of structural variation ≥12 kb between the two species. Our analysis yielded a total of 651 putative sites of chimpanzee deletion (n = 293), insertions (n = 184), and rearrangements consistent with local inversions between the two genomes (n = 174). We validated a subset (19/23) of insertion and deletions using PCR and Southern blot assays, confirming the accuracy of our method. The events are distributed throughout the genome on all chromosomes but are highly correlated with sites of segmental duplication in human and chimpanzee. These structural variants encompass at least 24 Mb of DNA and overlap with >245 genes. Seventeen of these genes contain exons missing in the chimpanzee genomic sequence and also show a significant reduction in gene expression in chimpanzee. Compared with the pioneering work of Yunis, Prakash, Dutrillaux, and Lejeune, this analysis expands the number of potential rearrangements between chimpanzees and humans 50-fold. Furthermore, this work prioritizes regions for further finishing in the chimpanzee genome and provides a resource for interrogating functional differences between humans and chimpanzees.